Teaching English to Young Learners Through Songs - Setyaningsih, Ani (Journal of English and Education (JEE), 2007)
Globalisation brings a great impact on the use of English in any domains like business, education, IT and the like. English has become lingua franca one chooses to communicate with others having a different language. English has spread worldwide and this phenomenon has resulted in English teaching learning in primary level in many non- English-speaking countries. This brings a consequence to a crucial need in teachers' education. Teachers at the primary level need to develop both competence in English use and teaching skills to young learners regarding their special characteristics. Theories in  children development is needed by teachers to meet the special needs of children. One method suggested to meet those needs through songs" Songs help children to internalize some words and sentences in the new language. Songs also provide a link with their everyday lives and be fun. Songs can be used at any level of ages at any stage in a lesson. In the beginning of a lesson songs can be used to mark the change from one topic to another. Songs can be a break from another more concetrate activity in the middle of a lesson and used to round a lesson of the end.